2013
DOI: 10.22499/2.6302.001
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the initial ACCESS numerical weather prediction system

Abstract: The Australian Community Climate and Earth-System Simulator (ACCESS) is a coupled climate and earth system simulator being developed as a joint initiative of the Bureau of Meteorology and CSIRO in cooperation with the university community in Australia. The main aim of ACCESS is to develop a national approach to climate and weather prediction model development. Planning for ACCESS development commenced in 2005 and significant progress has been made subsequently. ACCESS-based numerical weather prediction (NWP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 32 publications
1
112
0
Order By: Relevance
“…At short term (0-24 h), the best results in intensity and position forecasts are from the two limitedarea models owing to vortex bogusing. This is consistent with recent statistics obtained over the Australian region using a sample of 22 forecasts of two major TCs (see Table 4 of Davidson et al 2014): the Australian Community Climate and Earth System Simulator (ACCESS-A; Puri et al 2013) showed an average mean absolute error of 11 hPa and 117 km at the initial time of the forecast, while the average error was reduced to 7 hPa and 30 km in the version of the model that uses vortex bogusing (ACCESS-TC; Davidson et al 2014). However, at longer ranges (48-72 h), ECMWF performs better thanks to a more coherent representation of the interaction between the storms and their large-scale environments.…”
Section: Tc Analysis Uncertainty Over the Southwest Indian Oceansupporting
confidence: 91%
“…At short term (0-24 h), the best results in intensity and position forecasts are from the two limitedarea models owing to vortex bogusing. This is consistent with recent statistics obtained over the Australian region using a sample of 22 forecasts of two major TCs (see Table 4 of Davidson et al 2014): the Australian Community Climate and Earth System Simulator (ACCESS-A; Puri et al 2013) showed an average mean absolute error of 11 hPa and 117 km at the initial time of the forecast, while the average error was reduced to 7 hPa and 30 km in the version of the model that uses vortex bogusing (ACCESS-TC; Davidson et al 2014). However, at longer ranges (48-72 h), ECMWF performs better thanks to a more coherent representation of the interaction between the storms and their large-scale environments.…”
Section: Tc Analysis Uncertainty Over the Southwest Indian Oceansupporting
confidence: 91%
“…As can be seen via comparison with Fig. 1 of Puri et al (2013), the ACCESS1.3 configuration is a key step on the way to attaining a full earth system model as laid out in the original ACCESS project plan. 5 GA1.0 comprises a suite of atmospheric model implementations sharing a common physics, and, of relevance here, includes the atmospheric component of the UK Met Office's HadGEM3(r1.1) coupled model (Arribas et al2011, Hewitt et al 2011 Though the component codes may be different, the ACCESS modelling program builds on a long history of weather and climate modelling in Australia.…”
Section: Model Descriptionmentioning
confidence: 99%
“…All these uncertainties impact our ability to project climate change at the regional level and evaluate the potential impact on the Australian community, and to respond to the risks in an informed manner. Puri et al (2013) have outlined the development of a new Australian capacity in weather and climate simulation, the Australian Community Climate and Earth System Simulator (ACCESS). A major goal of ACCESS is to provide state-ofthe-art climate modelling capacity to support Australian research aimed at addressing uncertainties such as those above.…”
Section: Introductionmentioning
confidence: 99%
“…For the Bureau's implementation of the algorithm, the NWP data are primarily derived from the Australian Community Climate and Earth-System Simulator (ACCESS) model [Puri et al, 2013]. In particular, the regional version (ACCESS-R) of the model is used [National Meteorological and Oceanographic Centre, 2013].…”
Section: Nwp Datamentioning
confidence: 99%